Cross-Linked Nanohybrid Polymer Electrolytes With POSS Cross-Linker for Solid-State Lithium Ion Batteries - Zhang, Jinfang; Li, Xiaofeng; Li, Ying; Wang, Huiqi; Ma, Cheng; Wang, Yanzhong; Hu, Shengliang; Wei, Weifeng (Frontiers in Chemistry, 2018)
A new class of freestanding cross-linked hybrid polymer electrolytes (HPEs) with POSS as the cross-linker was prepared by a one-step free radical polymerization reaction. Octavinyl octasilsesquioxane (OV-POSS) with eight functional corner groups was used to provide cross-linking sites for the connection of polymer segments and the required mechanical strength to separate the cathode and anode. The unique cross-linked structure offers additional free volume for the motion of EO chains and provides fast and continuously interconnected ion-conducting channels along the nanoparticles/polymer matrix interface. The HPE exhibits the highest ionic conductivity of 1.39 × 10−3 S cm−1, as well as excellent interfacial compatibility with the Li electrode at 80°C. In particular, LiFePO4/Li cells based on the HPE deliver good rate capability and long-term cycling performance with an initial discharge capacity of 152.1 mAh g−1 and a capacity retention ratio of 88% after 150 cycles with a current density of 0.5 C at 80°C, demonstrating great potential application in high-performance LIBs at elevated temperatures.